Deoxycholic acid enhancement of lymphocyte migration through direct interaction with the intestinal vascular endothelium. Issue 9 (14th April 2021) - Shibuya, Naoki; Higashiyama, Masaaki; Akita, Yoshihiro; Shirakabe, Kazuhiko; Ito, Suguru; Nishii, Shin; Mizoguchi, Akinori; Inaba, Kenichi; Tanemoto, Rina; Sugihara, Nao; Hanawa, Yoshinori; Wada, Akinori; et al.
Abstract: Background and Aim: The small intestine plays a central role in gut immunity, and enhanced lymphocyte migration is involved in the pathophysiology of various enteropathy. Bile acid (BA) is closely related to lipid metabolism and gut microbiota and essential for gut homeostasis. However, the effects of BA on gut immunity have not been studied in detail, especially on the small intestine and lymphocyte migration. Therefore, we aimed to investigate the effect of BA on small intestinal lymphocyte microcirculation. Methods: The effect of deoxycholic acid (DCA), taurocholic acid (tCA), or cholic acid (CA) on the indomethacin (IND)‐induced small intestinal enteropathy in mice was investigated. Lymphocyte movements were evaluated after exposure to BA using intravital microscopy. The effects of BA on surface expression of adhesion molecules on the vascular endothelium and lymphocytes through BA receptors were examined in vitro . Results: IND‐induced small intestinal enteropathy was histologically aggravated by DCA treatment alone. The expression of adhesion molecules ICAM‐1 and VCAM‐1 was significantly enhanced by DCA. Exposure to DCA increased lymphocyte adhesion in the microvessels of the ileum, which was partially blocked by anti‐α4β1 integrin antibody in vivo . The expression of ICAM‐1 and VCAM‐1 was significantly enhanced by DCA in vitro, which was partially suppressed by the sphingosine‐1‐phosphate receptor 2 (S1PR2) antagonist. The S1PR2 antagonist significantly ameliorated IND‐induced and DCA‐exaggerated small intestinal injury. Conclusion: DCA exacerbated IND‐induced small intestinal enteropathy. DCA directly acts on the vascular endothelium and enhances the expression levels of adhesion molecules partially via S1PR2, leading to enhanced small intestinal lymphocyte migration.